2009
DOI: 10.1080/03093640802613237
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laterally Wedged Foot Orthoses on Rearfoot and Hip Mechanics in Patients with Medial Knee Osteoarthritis

Abstract: The purpose of this study was to examine the effects of laterally wedged foot orthotic devices, used to treat knee osteoarthritis, on frontal plane mechanics at the rearfoot and hip during walking. Thirty individuals with diagnosed medial knee osteoarthritis were recruited for this study. Three dimensional kinematics and kinetics were recorded as the subjects walked in the laboratory at an intentional walking speed. Peak eversion, eversion excursion and peak eversion moment were increased while the peak knee a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
49
4
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 24 publications
3
49
4
1
Order By: Relevance
“…Four studies reported the use of the ACR criteria (31,(34)(35)(36), with 10 stating cutoffs regarding the severity of knee pain (13,14,21,31,32,34,(36)(37)(38)(39), most commonly .3 of 10 on a visual analog scale (13,14,21,31,32,34,37). This definition varied across studies according to the activity, with pain recalled during walking (29,38), walking 2 blocks and/or climbing stairs (36), weight-bearing activities (37), and on most days of the past month (21,32,39). All studies included radiographic assessment of tibiofemoral OA.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Four studies reported the use of the ACR criteria (31,(34)(35)(36), with 10 stating cutoffs regarding the severity of knee pain (13,14,21,31,32,34,(36)(37)(38)(39), most commonly .3 of 10 on a visual analog scale (13,14,21,31,32,34,37). This definition varied across studies according to the activity, with pain recalled during walking (29,38), walking 2 blocks and/or climbing stairs (36), weight-bearing activities (37), and on most days of the past month (21,32,39). All studies included radiographic assessment of tibiofemoral OA.…”
mentioning
confidence: 99%
“…All studies included radiographic assessment of tibiofemoral OA. This was most commonly defined as Kellgren/Lawrence grade 2 and above (13,14,21,29,31,32,34,37,38,40). Presence of medial joint space narrowing greater than lateral (13,32, 29,32,33,35,36,38,39) and/or varus knee alignment (13,30, 36,40,41) were used to limit participants to those with medial tibiofemoral OA.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment goal in varus knee OA, by means of surgical (eg, high tibial osteotomy) [16,22,61] and nonsurgical methods (eg, wedging foot orthoses, unloading knee braces) [10,42,58], is to reduce deviation of the mechanical axis of the lower extremity from the knee joint center. However, the 'mechanical axis' is a static 2-D radiographic measurement that varies with foot position [32] and weightbearing status (eg, single versus doublelimb support) [70], and it might not always correlate with complex 3-D loading or dynamic function of the knee [2,28,40].…”
Section: Discussionmentioning
confidence: 99%